Comparison of psychometric properties of multiple-choice test using confidence and number right scoring among senior secondary school students in Ibadan metropolis (2019)
This study investigated the comparison of psychometric properties of multiple-choice test using confidence and number right scoring among senior secondary school students in Ibadan metropolis. The study adopted a descriptive design of survey type. The population for the study consisted of Senior Secondary School two (SSS II) students in Ibadan Metropolis, Oyo state, Nigeria. A sample of 400 Agricultural science students was selected across 4 Local Government Areas in Ibadan metropolis, using purposive (mainly Agricultural Science Students) and random sampling techniques. The instrument used for the study was Agricultural science Multiple-choice Test. The 50 items Agricultural Science 4-option test was administered on the Students. Data collected were analyzed using paired samples t-test, Kuder-Richardson (KR-21), Cronbach alpha, and Fisher z-test. The results obtained revealed that significant difference existed in the difficulty indices with Number Right (NR) and Confidence Scoring Method (CSM) with mean of 55.42 and 44.01 respectively. Also, there was a significant difference in the CSM and NR in the discrimination indices with NR and CSM has mean of 0.57 and 0.52 respectively. It was found that NR significantly improved the difficulty and discrimination indices. Furthermore, the finding revealed that there was no significant difference between NR and CSM in the reliability coefficient. Based on these findings, it was recommended that number right scoring method should be used to assess Agricultural science students’ performances because it makes test item appear moderate in terms of difficulty level and is very easy for students to guess the items right.